Grammatical boundaries in phonology - Basbøll, Hans (Annual Report of the Institute of Phonetics University of Copenhagen, 1975)
This paper1 is divided into two main parts: (1) on grammatical boundaries in generative phonology, including an overview of boundaries in the phonology of French, and (2) which concentrates on the evidence for grammatical boundaries, and where both French and Danish examples are discussed. This bipartition is mainly made for expository reasons, and there is a considerable overlapping in the contents of the two sections.